Ripening of Sudanese Braided (Muddaffara) Cheese Manufactured from Raw or Pasteurized Milk: Effect of Heat Treatment and Salt Concentration on the Physicochemical Properties - Mohamed O. E. Altahir; Elgasim A. Elgasim; Isam A. Mohamed Ahmed (International Journal of Food Science)
The objective of the study was to investigate the interactive effect of heat treatment (raw or pasteurized milk), ripening in salted whey (SW) and storage period for up to 3 months on the physicochemical properties of Sudanese braided cheese (SBC). Braided cheeses were manufactured from raw (BCRM) and pasteurized (BCPM) milk and ripened in SW (0%, 5%, and 10% salt) for up to 90 days. All the treatments significantly (P≤0.05) affected the physicochemical characteristics of SBC. The total solid, protein, and fat contents of BCRM or BCPM decreased (P≤0.05), whereas their TA, SN, and salt contents increased significantly (P≤0.05) as storage period and the salt level of the whey were elevated. Both FRI and SRI of BCRM and BCPM increased with the increase in storage period and the salt level of the whey. For SN, FRI, SRI, pH, and moisture contents the magnitude of the change was more pronounced in BCRM than in BCPM, while for protein, fat, salt, and TS contents, the opposite was true; that is, the magnitude of the change was more pronounced in BCPM than in BCRM. Further studies are required to standardize muddaffara cheese manufacturing procedure particularly in rural areas.